(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
A disaster is a major issue that affects a community or society for an extended period of time and results in widespread loss of people, property, economic resources, or the environment. The character of people who have experienced disasters frequently in the environment tend to think that disasters are a normal occurrence and feel like they already know everything, so they are passive in seeking disaster information. Hence, this study aimed to evaluate the information dissemination on disaster Preparedness of Barangay Public Safety officers in Novaliches Proper Quezon City. The main purpose of this is to formulate a proposed program that may help the administration to ensure safety and security when it comes to disaster preparedness. The study proposed a disaster theory about the Crunch and Release model, which indicates why the disaster occurs and how it can be avoided or reduced. The study revealed that the majority of the respondents encountered more challenges in disaster response vehicles, tents, and other temporary shelters and facilities for evacuation centers. While most of the residents are not participating when it comes to evacuation and program for disaster drills and also the data gathered, it is concluded that Barangay Novaliches Proper was needed to conduct a hazard map inspection and maintenance. The study suggested that the Barangay official may provide a recommendation letter to the local government to ask for help with their budget and expenses regarding vehicles and other facilities such as tents for evacuation. Also, keep the community well prepared by disseminating knowledge on how to be prepared when disaster happens. Residents can participate by attending seminars, programs, and training to raise disaster risk awareness and preparedness. Finally, the study suggested that BPSO conduct a further study that focuses on developing other materials and standard procedures like Fire, Earthquake, Typhoon, and Flood Drills. To better respond to and manage the immediate aftermath of a disaster, whether it is human-induced or brought on by natural hazards, communities or individuals take a number of precautions in advance.